THE EFFECT OF SERVICE QUALITY AND PRICE ON THE PURCHASE DECISION OF AQU TOUR UMRAH PACKAGES - Adwimurti, Yudhistira; Selfiani , Selfiani; Prihanto, Hendi (Graduate Program of Universitas Tarumanagara, 2023)
The aim of this research was to assess the impact of Service Quality and Price on the decision to purchase Umrah packages at PT. Afdhol Qurun Utama, both individually and collectively. This research employed a quantitative approach, specifically an associative hypothesis. The research population included all consumers who had previously bought Umrah packages from PT. Afdhol Qurun Utama. Sample selection was done through random sampling, utilizing the Slovin formula, resulting in a sample size of 187 respondents. Data were collected through various methods, including field research (questionnaires), observation, and library research, with a focus on ensuring validity and reliability. The analysis methods encompassed descriptive statistics, hypothesis testing (t-test), coefficient of determination (R2), and F-test, all performed with IBM SPSS Version 26 software. The findings from the analysis reveal that Service Quality has a statistically significant positive influence on purchasing decisions when considered individually. Similarly, the Price variable, when examined independently, also exerts a statistically significant positive impact on purchasing decisions. When examined together, both Service Quality and Price collectively have a statistically significant positive impact on the purchasing decisions regarding Umrah packages at PT. Afdhol Qurun Utama (AQU Tour & Travel).